Normative Analysis Of Maternity Leave Policy Implementation For Women Workers’ Rights In Bali - Sapariati, Anom; Widnyani, Ida Ayu Putu Sri; Dewi, Nyoman Diah Utari (Penerbit Goodwood, 2025)
Purpose: This study aimed to analyze the effectiveness of the maternity leave policy in Bali in safeguarding women workers' rights and to identify the normative challenges encountered in its implementation. Methodology: This study adopts a normative legal approach, focusing on literature studies and secondary data analysis, including an examination of relevant legislation, doctrines, and legal principles concerning maternity leave. Results: The findings indicate that while the maternity leave policy has a strong legal foundation, its implementation in Bali remains suboptimal, especially in the informal sector, where compliance with the regulation is low because of insufficient socialization and monitoring mechanisms. The implementation of the maternity leave policy in Bali requires strengthening through more effective socialization and monitoring, particularly in the informal sector, to ensure that women workers’ rights are fulfilled in accordance with existing regulations. Conclusion: Maternity leave in Bali is legally protected but poorly implemented, especially in informal sectors. It supports women’s health but does not solve wage inequality or unequal domestic roles. Stronger enforcement and shared caregiving are key to achieving true gender equality. Limitations: This study is limited to a normative approach with a focus on Bali; therefore, its findings may not be fully generalizable to other contexts. Contribution: This study provides insights for local policymakers on the importance of enhancing maternity leave policy implementation, particularly to support female workers' rights in Bali.